2007
DOI: 10.14723/tmrsj.32.317
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Sensing Using Surface Plasmon Excitation in Fluorescent Microsphere Films

Abstract: In this study, thin films of 100-nm. polystyrene (PS) microspheres mixed with polyvinyl alcohol (PV A) were prepared, and changes in the attenuated total reflection (ATR) using surface plasmon (SP) excitation due to humidity adsorption were investigated. The PS microspheres contained luminescent dyes, and SP emission light due to these dyes was also observed. The sample configuration was prism /Ag film (50 nm) I sphere film structure. The ATR dip and SP emission peak angles shifted in line with the adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In the ATR Kretschmann configuration, part of the SP energy can be converted to far-field light (SP emission light). [5][6][7][8] In this study, SP emission light was also observed, as shown in Fig. 1.…”
Section: Sp Emission Lightsupporting
confidence: 61%
See 4 more Smart Citations
“…In the ATR Kretschmann configuration, part of the SP energy can be converted to far-field light (SP emission light). [5][6][7][8] In this study, SP emission light was also observed, as shown in Fig. 1.…”
Section: Sp Emission Lightsupporting
confidence: 61%
“…Emission light was observed as a function of the emission angle e , and could be strongly observed at approximately the SP resonant angles. [5][6][7][8] SP emission light has wavelength components of dye photoluminescence. In the measurement, emission light produced by SPs being excited owing to surface roughness is also observed, even with no dye contribution.…”
Section: Sp Emission Lightmentioning
confidence: 99%
See 3 more Smart Citations